(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Epilepsy is a widespread chronic neurological disease. The problems for people with epilepsy go far beyond seizures. Comorbidities associated with epilepsy are very common and often cause more problems for patients than the seizures themselves. Although seizures are the most prominent clinical manifestation of epilepsy, people with epilepsy are at risk not only for seizures, but also for a variety of health problems. Both children and adults with epilepsy often complain of memory impairment. It is generally accepted that cognitive impairment in epilepsy is multifactorial. Components that impair cognitive function include active seizures and in particular generalized tonic-clonic seizures, traumatic brain injury, structural epilepsy, and drug therapy. Cognitive impairment is very often present already during the onset of epilepsy.